The root lesion nematodes of banana: Pratylenchus coffeae (Zimmermann, 1898) Filip. & Schu. Stek., 1941, Pratylenchus goodeyi Sher & Allen, 1953 - Bridge, J.; Fogain R.; Speijer, P.R.; International Plant Genetic Resources Institute; International Network for the Improvement of Banana and Plantain (1997)
Musa pest fact sheet on the root lesion nematodes of banana : Pratylenchus coffeae and Pratylenchus goodeyi. It describes the latest information on the distribution and symptoms of these parasites of Musa and their control and invites collaboration in ongoing research.